A Population Based Analysis of Melanoma of the External Ear. Issue 2 (February 2018) - Patel, Tapan D.; Chin, Oliver Y.; Baredes, Soly; Eloy, Jean Anderson; Ying, Yu-Lan Mary
Abstract : Objective: Malignant melanoma accounts for nearly 75% of all skin cancer deaths, and the incidence is on the rise in the United States. External ear melanoma (EEM) is rare, and there is little long-term data regarding the clinical behavior of this melanoma site. This study analyzes the demographic, clinicopathologic, and survival characteristics of EEM. Methods: The SEER database was queried for EEM cases from 1973 to 2012 (8, 982 cases). Data analyzed included patient demographics, incidence trends, and survival outcomes. Results: External ear melanoma occurred most frequently in the sixth and seventh decades of life. Mean age at diagnosis was 65.5 (±16.8) years. However, the incidence of EEM in adolescents and young adults (ages 15–39 yr) has increased by 111.9% from 1973 to 2012. There was a strong male predilection with a male-to-female ratio of 6.40:1. The most common histologic subtype was malignant melanoma, NOS (46.8%), followed by superficial spreading melanoma (21.4%), and lentigo maligna melanoma (17.9%). The majority of cases were localized at the time of presentation (88.0%), with rare distant metastasis (1.9%). The most common treatment modality was surgery alone (97.6%), followed by surgery with radiotherapy (2.3%). Ten-year disease-specific survival was better among those treated with surgery alone (90.7%), than those treated with surgery with radiotherapy (37.1%) ( p  < 0.0001). Increasing Breslow's thickness and presence of an ulcerating lesion were both associated with poorer survival ( p  < 0.0001). Conclusion: This study represents the largest cohort of EEM. It has an excellent survival outcome with surgery being the treatment of choice. Abstract : Supplemental Digital Content is available in the text